Gravimetrical investigation of ice-rich permafrost within the Rock Glacier Murtèl-Corvatsch (Upper Engadin, Swiss Alps) - Vonder Mühll, Daniel; Klingelé, Emile E. (Permafrost and Periglacial Processes, 1994)
ISSN:1045-6740 ISSN:1099-1530